Kontekstualisasi Ayat Pidana Pencurian Dalam Hukum Positif Indonesia - Candra, Marli; Najib, M. Ainun (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2024)
Research Objective: This study investigates the significant abandonment of Islamic Criminal Law by examining its adaptability to contemporary contexts. It seeks to challenge the assumption that this legal framework is separate from modern legal systems through a historical analysis of Islamic jurisprudential influences on global punishment frameworks. Research Methodology: Employing a normative legal framework, the research adopts both conceptual and comparative approaches, specifically analyzing theft punishments within Islamic criminal law, Indonesian positive law, and Iranian positive law. Results: The comparative analysis reveals that, although all three legal systems share a common objective of deterrence, they employ distinct methodologies for punishment: Indonesian law predominantly utilizes imprisonment, Islamic law prescribes hand-cutting as a form of deterrent, and Iranian law implements a graduated system that ranges from finger-cutting to imprisonment. Findings and Implications: This research demonstrates that, despite the methodological differences in punishment approaches, each legal system bases its sentencing decisions on contextual factors, including the nature of the crime, the offender's background, and specific circumstances. Conclusion: While these legal systems share a fundamental goal of deterrence, they reflect different philosophical frameworks and cultural contexts. This underscores the idea that Islamic Criminal Law can be interpreted in a contextual manner, despite its distinctive punishment methods. Contribution: This study enriches jurisprudential discourse by challenging misconceptions regarding the contemporary relevance of Islamic Criminal Law. Limitations: The study's emphasis on a single category of offense restricts a comprehensive analysis of broader criminal law approaches. Suggestions: Future research should expand comparative analyses to encompass additional legal systems and a wider range of offenses